Prospective Follow-up of Intramedullary Slitlike Cavities: A Consecutive Series of 48 Patients - Faillot, Matthieu; Morar, Silvia; Delphine, Sebastien; El-Mendili, Mounir; Ducreux, Denis; Parker, Fabrice; Aghakhani, Nozar (Frontiers in Neurology, 2020)
Object: Predicting whether intramedullary slitlike cavity (SC) will worsen over time or remain stable is an outstanding clinical challenge. The aim of this study was to identify early features of SC (clinical and magnetic resonance imaging [MRI] findings). Methods: We prospectively included all patients referred to our institution following the discovery of a SC and divided them in two groups: typical SC (defined as a cavity spanning fewer than three vertebrae, not enlarging the spinal cord, and located at the midline between the anterior third and posterior two-thirds of the spinal cord) or atypical SC (all others). Clinical evolution and changes in MRI features were evaluated during follow-up. In some patients, diffusion tensor imaging was performed and cervical cord cross-sectional area was analyzed. Results: A total of 48 consecutive patients were included in the study. The mean follow-up was 58 months. Of the seven patients presenting with deficits at first consultation, two worsened and five remained stable. Of the 41 patients without deficits, seven worsened and 34 remained stable. None of the patients developed severe motor deficits or experienced enlargement of the cavity; 7% of patients who presented with typical SC worsened compared with 35% with atypical SC. The negative predictive value was 0.93 (P = .02). Conclusion: Most patients remained stable and a subset of patients developed minor motor deficits. For clinical management, we propose surveillance of patients with a typical SC and close follow-up of those with an atypical SC and/or presenting with deficits.